Development of Leaflet Media in Arabic Learning for Second Grade at MTs Al Falaah Pandak Bantul : Pengembangan Media Leaflet dalam Pembelajaran Bahasa Arab pada Siswa Kelas VIII di MTs Al Falaah Pandak Bantul - Nurhadi Nurhadi; Hamdan Hadi Purnomo (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2023)
Abstract The lack of usage of Arabic learning media at MTs Al Falaah Pandak is the background for this study. Therefore, this study aims to develop Leaflet learning media, determine the feasibility of Leaflet media, the practicality of Leaflet, and the effectiveness Leaflet media in learning Arabic for second grade at MTs Al Falaah Pandak Bantul. The type of this study is Research and Development using Borg & Gall development model adapted and developed by Sugiono. The development model consists of potentials and problems, information gathering, product design, design validation, design revision, prooduct trial, product revision, and usage trial or field trial. Validation was carried out by media expert and material expert. The trial usage of product was carried out on 27 students, second grade of MTs Al Falaah Pandak Bantul. The Instrument used in collecting data consisted of feasibility testing instrument in form of expert validation sheets on instructional media, practically testing instrument in the form of studentsâ€™ response questionnaire, and effectiveness testing instrument in the form of student learning achievement test. Referring to feasibility trial data, the revised learning media is in the proper criteria. This is based on the assessment of material expert with a total score percentage of 94,5% and the assessment of media expert with a total score percentage of 92%. Meanwhile, the assessment of the level of practicality of learning media developed got the practical criteria with a percentage of total average test score of 90%. Then, the assessment of student learning outcome, it showed an average score of 84,81%, the number of students who completed the learning process was 24 people or 89% and 3 people or 11% of students was uncompleted. Keyword: Research and Development, Arabic Learning Media, Leaflet Ù…Ù„Ø®Øµ Ø®Ù„ÙÙŠØ© Ø§Ù„Ù…Ø³Ø£Ù„Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø£Ù‚Ù„ Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ÙÙ„Ø§Ø ÙÙ†Ø¯Ø§Ùƒ. Ùˆ Ù„Ø°Ù„ÙƒØŒ Ø£Ù‡Ø¯Ø§Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ ØªØ·ÙˆÙŠØ± ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ…ÙŠØ© LeafletØŒ Ù„ØªØ¹Ø±ÙŠÙ Ø£Ù‡Ù„ÙŠÙ‘Ø© ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ…ÙŠØ© LeafletØŒ Ù„ØªØ¹Ø±ÙŠÙ Ø¹Ù…Ù„ÙŠÙ‘Ø© ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ…ÙŠØ©Â Â LeafletØŒ ÙˆÙ„ØªØ¹Ø±ÙŠÙ ÙØ¹Ø§Ù„ÙŠØ© ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ…ÙŠØ© Â LeafletÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù…Ù† Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ÙÙ„Ø§Ø ÙÙ†Ø¯Ø§Ùƒ Ø¨Ù†ØªÙˆÙ„. ÙƒØ§Ù† Ù†ÙˆØ¹ Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ø¨ØØ« ÙˆØ§Ù„ØªØ·ÙˆÙŠØ± Ø¹Ù„Ù‰ Â Ø·Ø±Ø² Ø³ÙˆØºÙŠÙŠÙˆÙ†Ùˆ Â ÙˆØ§Ù„Ø°ÙŠ ØªØ·ÙˆÙŠØ±Ù‡ Ø¨ÙˆØ±Ùƒ & ÙƒØ§Ù„. ÙˆÙƒØ§Ù† Ø·Ø±Ø² Ø§Ù„ØªØ·ÙˆÙŠØ± ÙŠØªÙƒÙˆÙ‘Ù† Ù…Ù† Ù‚ÙˆØ© ÙˆÙ…Ø³Ø§Ø¦Ù„ØŒØ¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§ØªØŒ ØªØµÙ…ÙŠÙ… Ø§Ù„Ù…Ù†ØªØ¬ØŒ ØªØµØ¯ÙŠÙ‚ Ø§Ù„ØªØµÙ…ÙŠÙ…ØŒ ØªØØ³ÙŠÙ† Ø§Ù„ØªØµÙ…ÙŠÙ…ØŒ Ù…Ø¬Ø§Ø±Ø¨Ø© Ø§Ù„Ù…Ù†ØªØ¬ØŒ ØªØØ³ÙŠÙ† Ø§Ù„Ù…Ù†ØªØ¬ØŒ ÙˆÙ…Ø¬Ø§Ø±Ø¨Ø© Ø§Ù„Ø¥Ø³ØªÙ‡Ù„Ø§Ùƒ. Ø§Ù„ØªØµØ¯ÙŠÙ‚ Ø¹Ù„Ù‰ Ø£Ù‡Ù„ Ø§Ù„Ù…Ø§Ø¯Ø© ÙˆØ£Ù‡Ù„ Ø§Ù„ÙˆØ³ÙŠÙ„Ø©. ÙˆÙ…Ø¬Ø§Ø±Ø¨Ø© Ø§Ù„Ø¥Ø³ØªÙ‡Ù„Ø§Ùƒ Ù„Ù„Ù…Ù†ØªØ¬ ØªØ¹Ù‚Ø¯ Ø¹Ù„Ù‰ Ù¢Ù§ Ø·Ø§Ù„Ø¨Ù‹Ø§ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù…Ù†Â Ø¨Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ÙÙ„Ø§Ø ÙÙ†Ø¯Ø§Ùƒ . ØªØªÙƒÙˆÙ† Ø§Ù„Ø£Ø¯ÙˆØ§Øª Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ø¬Ù…Ø¹ Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„Ø¨ØØ« Ù…Ù† Ø£Ø¯Ø§Ø© Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„ØªØµØ¯ÙŠÙ‚ Ø¨Ø´ÙƒÙ„ Ø£ÙˆØ±Ø§Ù‚ ØªØÙ‚Ù‚ Ù„Ø£Ù‡Ø§Ù„ Ø¹Ù† Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© ØŒ Ùˆ Ø£Ø¯Ø§Ø© Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„Ø¹Ù…Ù„ÙŠ Ø¨Ø´ÙƒÙ„ Ø§Ø³ØªØ¨ÙŠØ§Ù†Ø§Øª Ø§Ø³ØªØ¬Ø§Ø¨Ø© Ø§Ù„Ø·Ù„Ø§Ø¨ØŒ Ùˆ Ø£Ø¯Ø§Ø© Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„ÙØ¹Ø§Ù„ÙŠØ© Ø¨Ø´ÙƒÙ„ Ø¥Ø®ØªØ¨Ø§Ø± Ø§Ù„ØªØØµÙŠÙ„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠ Ù„Ù„Ø·Ø§Ù„Ø¨ .Ø£Ø´Ø§Ø±Øª Ø¥Ù„Ù‰ Ø¨ÙŠØ§Ù†Ø§Øª ØªØ¬Ø±Ø¨Ø© Ø§Ù„ØªØÙ‚ÙŠÙ‚ØŒ ÙØ¥Ù† ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ù†Ù‚ØØ© Ù‚Ø¯ ÙƒØ§Ù† ÙÙŠ Ù…Ø¹ÙŠØ§Ø± Ø§Ù„ØÙ‚Ù‘. ÙˆØ°Ø§Ù„Ùƒ ÙŠØ¹ØªÙ…Ø¯ Ù‡Ø°Ø§ Ø¹Ù„Ù‰ ØªÙ‚ÙŠÙŠÙ… Ø£Ù‡Ù„ Ø§Ù„Ù…ÙˆØ§Ø¯ Ø¨Ù†Ø³Ø¨Ø© Ø¥Ø¬Ù…Ø§Ù„ÙŠØ© ØªØ¨Ù„Øº Ù©Ù¤ØŒÙ¥Ùª ÙˆØªÙ‚ÙŠÙŠÙ… Ø£Ù‡Ù„ Ø§Ù„Ø¥Ø¹Ù„Ø§Ù…ÙŠ Ø¨Ù†Ø³Ø¨Ø© Ø¥Ø¬Ù…Ø§Ù„ÙŠØ© ØªØ¨Ù„Øº Ù©Ù¢ÙªÂ . Ø¨ÙŠÙ†Ù…Ø§ ØªÙ‚ÙŠÙŠÙ… Ø§Ù„ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„Ø¹Ù…Ù„ÙŠ Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù…Ø·ÙˆØ±Ø© Ù‚Ø¯ ÙƒØ§Ù† ÙÙŠ Ù…Ø¹Ø§ÙŠØ± Ø¹Ù…Ù„ÙŠ Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ù†Ø³Ø¨Ø© Ø¥Ø¬Ù…Ø§Ù„ÙŠØ© Ù…Ù† Ù…ØªÙˆØ³Ø· â€‹â€‹Ù‚ÙŠÙ…Ø© Ø§Ù„ØªØ¬Ø±Ø¨Ø© Ø¨Ù†Ø³Ø¨Ø© Ù©Ù Ùª Ø«Ù… Ù„ØªÙ‚ÙŠÙŠÙ… Ù†ØªØ§Ø¦Ø¬ ØªØ¹Ù„Ù… Ø§Ù„Ø·Ù„Ø§Ø¨ Ø£Ø¸Ù‡Ø± Ø¨Ù…ØªÙˆØ³Ø· â€‹â€‹Ù‚ÙŠÙ…Ø©Ù¨Ù¤ØŒÙ¨Ù¡ÙªØŒ ÙƒØ§Ù† Ø¹Ø¯Ø¯ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø°ÙŠÙ† Ø£ÙƒÙ…Ù„ÙˆØ§ ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù… Ù¢Ù¤ Ø´Ø®ØµÙ‹Ø§ Ø£Ùˆ Ù¨Ù©Ùª ÙˆÙ„Ù… ÙŠÙƒÙ…Ù„ÙˆØ§ Ù…Ø§ ÙŠØµÙ„ Ø¥Ù„Ù‰ Ù£ Ø£Ø´Ø®Ø§Øµ Ø£Ùˆ Ù¡Ù¡Ùª Ù…Ù† Ø§Ù„Ø·Ù„Ø§Ø¨. Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© : Ø§Ù„Ø¨ØØ« ÙˆØ§Ù„ØªØ·ÙˆÙŠØ± ØŒ ÙˆØ³ÙŠÙ„Ø© ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©